Catabolism of l-rhamnose in A. nidulans proceeds via the non-phosphorylated pathway and is glucose repressed by a CreA-independent mechanism - MacCabe, Andrew P.; Ninou, Elpinickie I.; Pardo, Ester; Orejas, Margarita (Microbial cell factories, 2020)
l -rhamnose (6-deoxy-mannose) occurs in nature mainly as a component of certain plant structural polysaccharides and bioactive metabolites but has also been found in some microorganisms and animals. The release of l -rhamnose from these substrates is catalysed by extracellular enzymes including α- l -rhamnosidases, the production of which is induced in its presence. The free sugar enters cells via specific uptake systems where it can be metabolized. Of two l -rhamnose catabolic pathways currently known in microorganisms a non-phosphorylated pathway has been identified in fungi and some bacteria but little is known of the regulatory mechanisms governing it in fungi. In this study two genes ( lraA and lraB ) are predicted to be involved in the catabolism of l -rhamnose, along with lraC , in the filamentous fungus Aspergillus nidulans . Transcription of all three is co-regulated with that of the genes encoding α- l -rhamnosidases, i.e. induction mediated by the l -rhamnose-responsive transcription factor RhaR and repression of induction in the presence of glucose via a CreA-independent mechanism. The participation of lraA /AN4186 (encoding l -rhamnose dehydrogenase) in l -rhamnose catabolism was revealed by the phenotypes of knock-out mutants and their complemented strains. lraA deletion negatively affects both growth on l -rhamnose and the synthesis of α- l -rhamnosidases, indicating not only the indispensability of this pathway for l -rhamnose utilization but also that a metabolite derived from this sugar is the true physiological inducer.